Morphological Study of Human Parathyroid Glands A Postmortem Study - Mahbub, Sabiha; Ara, Shamim; Nurunnabi, Abu Sadat Mohammad; Alim, Abdul; Ahmed, Rukshana; Alam, Md Jahangir; Nahar, Yesmin (Bangladesh Journal of Anatomy, 2014)
Context: The parathyroid gland, the last major organ to be recognized in humans is an essential endocrine gland. The hormone secreted by the parathyroid gland provides a powerful mechanism for controlling extracellular calcium and phosphate concentration. Detailed morphological knowledge of parathyroid gland is essential for proper diagnosis and management of parathyroid diseases. Materials & Methods: A cross sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, on parathyroid glands of 60 (sixty) Bangladeshi people in different age groups. Total 207 (two hundred and seven) parathyroid glands were taken from these 60 (sixty) cadavers. The samples were collected from the unclaimed dead bodies were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. The samples were divided into three different age groups ranging from 15 to 75 years. The groups were group A (10-30 years), group B (31-60 years) and group C (61-90 years). All samples were studied morphologically. Results: In the present study of 60 cadavers, 207 parathyroid glands were identified in relation to posterior border of thyroid lobe. In this study the mean SD length of parathyroid glands ranged from 3.36 ± 1.11 to 9.25 ± 1.71 mm, breadth of parathyroid glands ranged from 2.50 ± 0.58 to 5.33 ± 1.53 mm and thickness of parathyroid glands ranged from 1.25 ± 0.50 to 2.83 ± 0.29 mm. DOI: http://dx.doi.org/10.3329/bja.v11i1.20503 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 15-18